A Needs for Mass Communication Development in Luang Prabang Province, Laos: A Case Study of the Department of Information, Culture, and Tourism - xaiyvong, chanthaphon (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aims to assess the needs for the development of media work within the Department of Information, Culture, and Tourism in Luang Prabang Province, Laos. A quantitative research method was employed, with the target group consisting of 29 employees from the department, including 10 females. Data were collected using a questionnaire, and analysis was conducted using SPSS to calculate the mean (μ) and standard deviation (σ). The findings revealed that the overall need for media development was high (μ = 4.42, σ = 0.63). The highest areas of need identified were the development of quality media (μ = 4.72, σ = 0.45), training to improve news content (μ = 4.55, σ = 0.63), and training to promote the party's policy guidelines (μ = 4.52, σ = 0.63). Other high-priority areas included the correction of media content (μ = 4.45, σ = 0.57), development of radio, television, film, and print media (μ = 4.45, σ = 0.63), use of production equipment (μ = 4.41, σ = 0.63), development of coordination systems (μ = 4.28, σ = 0.65), creation of media information infrastructure (μ = 4.24, σ = 0.96), and the development of systems for receiving and distributing print media (μ = 4.17, σ = 0.66).